1998
DOI: 10.1111/j.1572-0241.1998.442_l.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: A Risk Factor for Severe Acute Biliary and Alcoholic Pancreatitis

Abstract: Obesity may predispose to a complicated course of AP, especially if it is secondary to alcohol or gallstones. Further studies are needed to establish the precise prognostic value of obesity in AP, as well as the pathogenic mechanisms involved in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(27 citation statements)
references
References 25 publications
2
24
0
1
Order By: Relevance
“…Concerning the etiology, in this study, acute biliary pancreatitis accounted for 47.5% of all cases which is in line with results of earlier reports [8, 9]. Moreover, it was not surprising that alcohol was not a leading cause of acute pancreatitis, reflecting the fact that the level of alcohol consumption of 4.89 liters per capita in China was much lower when compared with 10.29 liters per capita in industrialized countries [10].…”
Section: Discussionsupporting
confidence: 79%
“…Concerning the etiology, in this study, acute biliary pancreatitis accounted for 47.5% of all cases which is in line with results of earlier reports [8, 9]. Moreover, it was not surprising that alcohol was not a leading cause of acute pancreatitis, reflecting the fact that the level of alcohol consumption of 4.89 liters per capita in China was much lower when compared with 10.29 liters per capita in industrialized countries [10].…”
Section: Discussionsupporting
confidence: 79%
“…Hypertriglyceridemia is crucially involved in obesity, which increases the risk of lung, rectal, and thyroid cancer. Clinical studies have clearly shown that obesity leads to increased severity of acute pancreatitis [8][9][10][11], and obesity appears to confer an increased risk of pancreatic cancer [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…As an independent prognostic factor for the worse outcome of AP, obesity has been considered to be related with a higher incidence of SAP, local and systemic complications, and higher mortality rates; however, these studies have flaws. One of the studies included in a previous meta-analysis had defined obesity as a BMI >25, which was different from their inclusion criteria [12]. In addition, 3 new prospective studies were published after the recent meta-analysis in 2006.…”
Section: Discussionmentioning
confidence: 99%